2016
DOI: 10.1051/0004-6361/201628159
|View full text |Cite
|
Sign up to set email alerts
|

Determining protoplanetary disk gas masses from CO isotopologues line observations

Abstract: Context. Despite intensive studies of protoplanetary disks, there is still no reliable way to determine their total (gast+dust) mass and their surface density distribution, quantities that are crucial for describing both the structure and the evolution of disks up to the formation of planets. Aims. The goal of this work is to use less abundant CO isotopologues, such as 13 CO, C 18 O and C 17 O, whose detection is routine for ALMA, to infer the gas mass of disks. Isotope-selective effects need to be taken into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
242
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(249 citation statements)
references
References 56 publications
6
242
1
Order By: Relevance
“…In addition, high mass disks have larger densities, which decreases the gas temperature in the disk. Miotello et al (2016) found a similar decrease in line luminosity for 13 CO and C 18 O for high mass disks, which they attributed to optical depth for 13 CO and increased freeze-out for C 18 O.…”
Section: Hd Flux Vs Disk Gas Massmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, high mass disks have larger densities, which decreases the gas temperature in the disk. Miotello et al (2016) found a similar decrease in line luminosity for 13 CO and C 18 O for high mass disks, which they attributed to optical depth for 13 CO and increased freeze-out for C 18 O.…”
Section: Hd Flux Vs Disk Gas Massmentioning
confidence: 58%
“…A possible explanation can be found in the gas mass of the disk. Miotello et al (2014Miotello et al ( , 2016 show that for disks with M disk ≥ 7 · 10 −3 M freeze-out is the dominant process affecting the C 18 O flux, whereas isotope-selective photodissociation is more important for low mass disks (see, e.g., Fig. 3 in Miotello et al 2016).…”
Section: Case Study: Tw Hyamentioning
confidence: 99%
“…Note, however, that the gas mass is estimated from the CO line emissions and as the authors noted, whether the large dust-togas mass ratio indicates rapid gas loss or depletion of CO by chemical evolution is unclear (see also Miotello et al 2016). Note also that the age of the objects are 1 3 Myr -and they are not in the Class 0/I phase.…”
Section: Comparison To Observationsmentioning
confidence: 95%
“…A significant caveat to our derived gas mass is that it depends inversely on the CO/H 2 abundance ratio, which we assume to be ISM-like ∼10 −4 . Furthermore, recent work by Miotello et al (2016) suggests that a more complex analysis is required to accurately determine disk gas masses.…”
Section: ( )mentioning
confidence: 99%